INNOVATIONS IN TEACHING YOUNG LEARNERS - NORMATOVA YULDUZ NURNAZAROVNA; RAXIMOVA GULCHEXRA OBIDJONOVNA (International Journal of Innovations in Engineering Research and Technology, 2021)
The significance of facilitating the learning and taking into account the way they learn by people involved in the teaching-learning process and implementing it into the teaching practices for young learners is discussed in the article.